Identification of humic-like substances (HULIS) in oxygenated organic aerosols using NMR and AMS factor analyses and liquid chromatographic techniques - M. Paglione; A. Kiendler-Scharr; A. A. Mensah; E. Finessi; L. Giulianelli; S. Sandrini; M. C. Facchini; S. Fuzzi; P. Schlag; A. Piazzalunga; E. Tagliavini; J. S. Henzing; et al. (Atmospheric Chemistry and Physics, 2014)
The atmospheric organic aerosol composition is characterized by a great diversity of functional groups and chemical species, challenging simple classification schemes. Traditional offline chemical methods identify chemical classes based on the retention behaviour on chromatographic columns and absorbing beds. Such an approach led to the isolation of complex mixtures of compounds such as the humic-like substances (HULIS). More recently, online aerosol mass spectrometry (AMS) was employed to identify chemical classes by extracting fragmentation patterns from experimental data series using statistical methods (factor analysis), providing simplified schemes for the classification of oxygenated organic aerosols (OOAs) on the basis of the distribution of oxygen-containing functionalities. The analysis of numerous AMS data sets suggested the occurrence of very oxidized OOAs which were postulated to correspond to HULIS. However, only a few efforts were made to test the correspondence of the AMS classes of OOAs with the traditional classifications from the offline methods. In this paper, we consider a case study representative of polluted continental regional background environments. We examine the AMS factors for OOAs identified by positive matrix factorization (PMF) and compare them to chemical classes of water-soluble organic carbon (WSOC) analysed offline on a set of filters collected in parallel. WSOC fractionation was performed by means of factor analysis applied to proton nuclear magnetic resonance (NMR) spectroscopic data, and by applying an ion-exchange chromatographic method for direct quantification of HULIS. Results show that the very oxidized low-volatility OOAs from AMS correlate with the NMR factor showing HULIS features and also with true "chromatographic" HULIS. On the other hand, UV/VIS-absorbing polyacids (or HULIS {sensu stricto}) isolated on ion-exchange beds were only a fraction of the AMS and NMR organic carbon fractions showing functional groups attributable to highly substituted carboxylic acids, suggesting that unspeciated low-molecular weight organic acids contribute to HULIS in the broad sense.